Harvester perceptions of pesticide impacts on snail collection along Cameroon’s Atlantic coast - Yannick Elysée Ewane Epée; Annick Niquaise Enangue Njembele; Christian Bernard Kaldjob Mbeh; Emmanuel Ndinga Go’o; Alexis Hamdja Ngoniri; Kingsley Agbor Etchu (PLoS ONE, 2026)
The coastal regions of Cameroon comprising South-West, Littoral, and South are major agricultural hubs and important zones for harvesting African giant land snails ( Achatinidae ). Snail collection provides both a vital protein source for local consumers and a source of income for harvesters. Agricultural intensification has increased pesticide use in these areas, raising concerns about potential impacts on snail populations and human health. This study assessed harvesters’ perceptions of how pesticides influence the quantity and size of snails collected. A total of 211 harvesters from six localities (Kribi, Buea, Limbe, Mbanga, Njombe-Penja, and Dibamba) were surveyed through interviews and participant observations. Descriptive statistics and regression models were applied to explore socio-demographic influences on perceptions. Results showed that while 58% of harvesters believed pesticides reduce snail size, 61% did not perceive an effect on snail quantity. Snail collection was reported to be most successful during nocturnal periods and in October, aligning with ecological seasonality. Regression analysis revealed a weak but statistically significant association between perceptions of pesticide impacts and reported harvesting quantities ( R² = 0.065 ), with perceived effects on snail quantity emerging as the only significant predictor. Despite awareness of pesticide risks, 63% of respondents expressed no interest in snail farming, citing preference for wild harvesting. This study highlights local knowledge on pesticide risks but also reveals a gap between awareness and adaptive practices. Findings are framed as perceptions, not direct ecological measurements, and they underline the need for awareness campaigns, sustainable harvesting practices, and supportive policies for alternative snail production systems.